2019
DOI: 10.1080/21691401.2019.1613418
|View full text |Cite
|
Sign up to set email alerts
|

Paeonol prevents IL-1β-induced inflammatory response and degradation of type II collagen in human primary chondrocytes

Abstract: Li (2019) Paeonol prevents IL-1β-induced inflammatory response and degradation of type II collagen in human primary chondrocytes, Artificial ABSTRACT Osteoarthritis (OA) is a common joint disease for which a safe and reliable treatment has yet to be developed. Here, we demonstrated the potential benefit of treatment with paeonol, a derivative of Paeonia suffruticosa, in the treatment and prevention of OA. Chondrogenic cell line ATDC5 cells were cultured with IL-1b and the effects of paeonol were assessed throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…The results of the present study have shown that paeonol prevents MTX-induced NOX-2 increase. In agreement with these results, paeonol decreased NOX-2 in rat primary microglia [39] and human primary chondrocytes [40]. In the current study, the ability of paeonol to significantly improve cardiac GSH level and SOD activity along with a decrease in MDA level is consistent with the finding of Li et al [41] who reported that paeonol significantly increased cardiac GSH level and SOD activity besides decreasing MDA level in isoproterenol-induced myocardial injury in rats.…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present study have shown that paeonol prevents MTX-induced NOX-2 increase. In agreement with these results, paeonol decreased NOX-2 in rat primary microglia [39] and human primary chondrocytes [40]. In the current study, the ability of paeonol to significantly improve cardiac GSH level and SOD activity along with a decrease in MDA level is consistent with the finding of Li et al [41] who reported that paeonol significantly increased cardiac GSH level and SOD activity besides decreasing MDA level in isoproterenol-induced myocardial injury in rats.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, 100 μmol/L of Pae was considered to be the safest concentration. In light of the results from previous studies [ 26 , 27 ], this concentration was used to explore the effects of Pae on mitochondrial homeostasis including mitochondrial dynamics and biogenesis in primary cardiomyocytes. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Paeonol displayed the same anti‐inflammatory effects in monosodium urate‐induced arthritis in rats (Chen et al, 2019) and lipopolysaccharides‐induced acute lung injury in mice (Wang, Zhu, et al, 2019). Moreover, paeonol protected against endoplasmic reticulum stress‐associated inflammation in lead‐stimulated kidneys (Liu et al, 2018) and IL‐1β‐induced inflammatory response in human primary chondrocytes (Wang, Xu, Kang, Zhang, & Li, 2019).…”
Section: Discussionmentioning
confidence: 99%